2020
DOI: 10.1016/j.dib.2020.106115
|View full text |Cite
|
Sign up to set email alerts
|

Data on antiplatelet aggregation, anticoagulation and antioxidant activities of Canna edulis Ker rhizome and its secondary metabolites

Abstract: Canna edulis Ker rhizome has been used in Traditional Vietnamese Medicine to prevent and treat heart diseases without thorough scientific evidence. The data presented in this article characterize the antiplatelet aggregation, anticoagulant and antioxidant activity of C. edulis rhizome extracts and the bio-guided isolation of bioactive compounds from the active fraction. The data on tested bioactivities of isolated compounds were also provided. The inhibitory effect on adenosin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
(4 reference statements)
0
0
0
Order By: Relevance
“…Canna edulis ( C. edulis ) is a perennial herb with high medicinal value. In traditional medicine, C. edulis is used to prevent and treat heart disease ( 7 ). C. edulis tubers contain several flavonoids with excellent gastroprotective effects, reducing the ulcer index and preventing pathology in alcoholic gastritis ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Canna edulis ( C. edulis ) is a perennial herb with high medicinal value. In traditional medicine, C. edulis is used to prevent and treat heart disease ( 7 ). C. edulis tubers contain several flavonoids with excellent gastroprotective effects, reducing the ulcer index and preventing pathology in alcoholic gastritis ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Modern pharmacological studies have found that Canna edulis Ker -Gawl protects the liver and gallbladder, treats acute jaundice hepatitis, has a gastroprotective efect [15], lowers blood pressure, lowers blood glucose, lowers blood lipids, prevents colon cancer [16], and cardiovascular disease [17,18] and has antioxidant activities [19,20]. Previous studies from our group [21][22][23][24][25] found that the resistant starch from the rhizome of Canna edulis Ker (Ce-RS3) after 11 weeks of Ce-RS3 intervention showed antidiabetic efects similar to metformin, signifcantly reduced blood glucose, reduced insulin resistance, increased glucose tolerance, and reduced pathological damage.…”
Section: Introductionmentioning
confidence: 99%